Influence of Rootstock Age and Methods of Epicotyl Grafting on the Success and Mortality of Grafts in "Dashehari" Mango - Poon, T.B.; Shrestha, G.K. (Journal of the Institute of Agriculture and Animal Science, 2002)
The present study was undertaken with the objectives of finding out an appropriate age of rootstock and methods of epicotyl grafting at fruit nursery block of Institute of Agriculture and Animal Science, Rampur, Nepal during 2000-2001. Three groups of rootstock-age and five methods of grafting were assessed in split plot design (3 x 5 factorial) with six replications. Of three groups of rootstock-age, three-week-old rootstock resulted in the maximum final success of grafts (30.0%); but two-week-old in the minimum (25.0%). The cumulative mortality of grafts was also the lowest (30.0%) in the three-week-old rootstock and the highest (44.0%) in two-week-old rootstock. Among five methods of grafting, modified veneer method gave significantly the highest of graft percent success (41.0%) followed by tongue (32.0%), while the lowest success (6.0%) was recorded in saddle method. More so, using modified veneer method, cumulative graft mortality was the lowest (23.6%); but was the highest (62.0%) in saddle method. Modified veneer onto three-week-old rootstock appeared to be the most potent treatment combination for getting high success of epicotyl grafts. However, further evaluation is needed to reconfirm the findings. J. Inst. Agric. Anim. Sci. 23:29-33